EVALUASI PELAKSANAAN PROGRAM ELIMINASI MALARIA DI KABUPATEN ACEH SINGKIL TAHUN 2018 - Afriadi, Afriadi; Suroyo, Razia Begum; Harahap, Juliandi (Universitas Prima Indonesia, 2020)
The success of the malaria elimination program in Kabuupaten Aceh Singkil, the Annual Parasite Incident (API) per 1000 population will reach 0%. Nowadays, the frequency of implementing the program has decreased so that it is suspected that it can cause people to suffer from malaria. The purpose of the study was to analyze the evaluation of the implementation of the malaria elimination program. This type of research is qualitative. The informants consisted of 5 key informants namely the person in charge of P2P, malaria management officers, village midwives and 4 main informants namely the head of the puskesmas and village head and 6 additional informants namely the community, pregnant women, cadres. Data were analyzed by interactive methods through the stages of data reduction, presentation and drawing conclusions. The results showed that blood tests were not carried out unless the community had a fever. Distribution of delivery nets, screening for pregnant women is reduced, and biological vector control is not monitored. Epidemiological surveillance and epidemic prevention are not carried out because there are no outbreaks so monitors are made in the form of monthly reports. Educational activities in the form of outreach continue to the present and responsibilities are more focused on village midwives/cadres. Training and guidance activities for officers have never been done. The percentage of API reaches 0% in 2018. It is recommended that health workers remain vigilant and prioritize programs supporting malaria elimination programs along with other health programs through community empowerment today.